Reduction of Carbon-Based Emissions using MgO Nanoparticle with Waste Cooking Oil Biodiesel in Diesel Engine. (13th June 2022) - Al Zubi, Mohammad A.; Jayaganthan, A.; Alimuddin,; Khan, Mohd Yunus; Kumar, Ravi; Singh, Bharat; Kakara, Vighneswara Rao
Abstract : Because biofuels are ecologically beneficial and might possibly lessen global warming, many academics are interested in studying them. Nanoparticles have been added to biodiesel to improve its performance as well as emissions. Diesel engine that operates on waste cooking oil biodiesel is the subject of the present research, which evaluates the impact of MgO nanoadditives on performance and emissions. Transesterification was done to convert waste cooking oil biodiesel into methyl ester. In the present study, SEM (scanning electron microscope), TEM (transmission electron microscope), and EDX spectroscopy are used for investigation of nanoadditives. The sample contained biodiesel blends with and without nanomagnesium oxide, as well as a combination of the two. According to the ASTM (American Society for Testing and Materials), the biodiesel produced from waste cooking oil met all fuel standards. The results of the testing were obtained by running a single-cylinder, 4-stroke diesel engine under a variety of loads. Using SEM analysis, the diameter of nanoparticles is found to be 20 nm to 38 nm. Magnesium oxide nanoparticles have been shown to include the elements oxygen, iron sulphide, silicon dioxide, and sodium. Oxygen accounted for about 50.74 percent of the samples, magnesium accounted for 45.36 percent, silicon dioxide accounted for 3.24 percent, and sodium accounted for 0.66 percent using EDX spectra. Magnesium oxide develops in unique shapes, with diameters varying from 9.24 to 14.94 nm, as seen in the TEM picture. An investigation found that B20 using 100 ppm MgO nanoparticles increases BTE (brake thermal efficiency) by 2.1 percent while simultaneously reducing SFC (specific fuel consumption) which was found to be ranging from 0.54 to 0.38 kg/kWh, respectively. B20 nanoparticles were used to reduce the amount of HC, CO, and smoke emitted by engines.